Production, Extracellular Purification, Characterization, and Cytotoxic Activity of L-Asparaginase Isolated from Locally Bacillus SPP - A. S., Mohammed (American Journal of Biology and Natural Sciences, 2025)
Ninety soil samples were obtained from diverse areas in Baghdad, and the examination revealed that 45 samples contained Bacillus spp. bacteria, and only 5 out of 45 showed the highest productivity in producing the L-asparaginase enzyme. The samples were named B1, B2, B3, B4, and B5, respectively. B4 produced the best enzyme activity (2.87 U/mg) after crude filtrate. This sample was also chosen to determine the optimal conditions to produce the best possible activity of the L-asparaginase after purification processes: the first step was L-asparaginase precipitated with 80% saturation ammonium sulfate, second purification step was used ion exchange chromatography employing) DEAE Cellulose( and the last step by gel filtration chromatography with Sephadex G-200. The enzyme specific activity was increased to 83.6 U /mg and 88.7 % enzyme recovery. After characterization and examination of the enzyme, It was revealed that the molecular weight that found for L-asparaginase from Bacillus sp. B4 was about 47,000 Dalton, The optimal pH for enzyme activity and stability ranged from pH8 to pH7 respectively. Optimum enzyme activity was obtained with 40 ºC temperature and L-asparaginase was stable at temperature from 40 to 70 ºC. also fond L-asparaginase activity was increased by add (1, 10 and 20mM) MnCl₂ and was inhibited by (1, 10 and 20Mm) CaCl₂,(4mM) cysteine and (4mM) EDTA, but it was not influenced by(1, 10 and 20mM) NaCl and KCl. The isolated L-asparginase had cytotoxic activity against the CCL-119 cell line while exhibiting reduced toxicity against normal cells, indicating its potential for further pharmaceutical use as an anticancer option.